Silica bodies of grasses from the "Cerrado". III - Silva, Sérgio Teixeira da; Labouriau, Luiz Gouvêa (Pesquisa Agropecuaria Brasileira, 2014)
Silica bodies in ten species of grasses from the Brazilian "Cerrados" (Andropogon carinatus Nees, Andropogon condensatus H.B.K., Andropogon semiberbis (Nees) Kunth, Andropogon villosus (Nees) Ekman, Panicum campestre Nees, Pardeum (Mesosetum) eriochrysoides N. & E., Panicum macranthum Trin, Panicum petrosum Trin, Sporobolus aeneus (Trin) Kunth and Trachypogon polymorphus Hack.) are studied. Herbarium samples of identified specimens were washed, charred at 200°C for 2 hours, digested with boiling 5N HCl, washed with water to absence of chlorides in the washings and ignited in porous clay crucibles at 800°C for 2 hours. Following this the silica was mounted on microscope slides in Canada balsam and drawings made with a camera lucida. Artifacts coming from particles imbeded in the crucibles were easily discriminated from opaline plant silica by the presence of a strong birefringence (which is entirely absent in plant silica). Several types of silica bodies were described and compared, as a contribution towards building a catalogue for the identification of "Cerrado" soil phytoliths.